1996
DOI: 10.1063/1.868857
|View full text |Cite
|
Sign up to set email alerts
|

The effect of streamwise braid vortices on the particle dispersion in a plane mixing layer. I. Equilibrium points and their stability

Abstract: The dynamics of small, heavy, spherical particles are investigated in an analytical model of the stretched counterrotating streamwise braid vortices commonly found in three-dimensionally evolving mixing layers. The flow field consists of two superimposed rows of Stuart vortices of opposite sign, with an additional two-dimensional strain field. The particle dynamics are determined by a balance of inertial, gravitational, and viscous drag forces, i.e., the dimensionless Stokes and Froude numbers, St and Fr, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…Recent reviews on the particle-demixing effects in turbulent two-phase flows can be found in [3][4][5]. Pioneering numerical simulations of tree-dimensional flows based on one-way coupling effects have been done by [1,[6][7][8][9]. However, the research on two-way momentum coupling effects in two-phase flow is still at a fundamental stage of study.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews on the particle-demixing effects in turbulent two-phase flows can be found in [3][4][5]. Pioneering numerical simulations of tree-dimensional flows based on one-way coupling effects have been done by [1,[6][7][8][9]. However, the research on two-way momentum coupling effects in two-phase flow is still at a fundamental stage of study.…”
Section: Introductionmentioning
confidence: 99%
“…It is theoretically possible to directly resolve the whole spectrum of turbulent scales using direct numerical simulation (DNS). Indeed, DNS has been successfully used on particle dispersion in temporal mixing layers [21,24] as well as in spatial mixing layer [13]. However, DNS is extremely expensive and requires huge computer power, as the grid density required is proportional to Re 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In Part I of the present investigation, 1 we introduced an analytical model of the counterrotating strained streamwise braid vortices commonly found in three-dimensionally developing plane mixing layers. [2][3][4][5][6] These flow structures are expected to result in a significant modification of the dominant two-dimensional particle dispersion mechanisms, [7][8][9][10][11][12] which are known to lead to the formation of bands of particles in the braid region.…”
Section: Introductionmentioning
confidence: 99%